Epifriedelanol is the key compound to antibacterial effects of extracts of Synadenium glaucescens (Pax) against medically important bacteria - Msengwa, Zaituni; Rwegoshora, Frank; David, Credo; Mwesongo, James; Mafuru, Magesa; Mabiki, Faith P.; Mwang’onde, Beda J.; Mtambo, Madundo M.; Kusiluka, Lughano J. M.; Mdegela, Robinson H.; Olsen, John E. (Frontiers in Tropical Diseases, 2023)
Introduction Synadenium glaucescens has been used for the treatment of bacterial infections in many parts of the world. We investigated the antibacterial and cytotoxicity activities of secondary metabolites of this plant. Methods Hexane, dichloromethane, methanol, and water were used as extraction solvents. The extract of the root bark was fractionated with ethyl acetate and methanol. The isolation of compounds from root barks, leaves and stem wood extracts were carried out using column chromatography. Antibacterial activities were characterized based on growth curves, killing curves and MIC determinations. Haemolytic effect towards sheep red blood cells (RBCs) was analysed with spectrophotometer at the wavelength of 540nm. Results and Discussion Extracts from whole root and root bark showed strong activity against Staphylococcus aureus, and Streptococci and Enterococci species, and moderate to weak activity against Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella species, Shigella sonnei and Yersinia enterocolitica. Staphylococcus aureus was the most susceptible, and E. coli and Klebsiella pneumonia were the least susceptible ones. Likewise, extracts, fractions, sub-fractions and epifriedelanol demonstrated bacteriostatic activity against S. aureus. The haemolytic activity of the extracts, fractions, sub-fractions and epifriedelanol was significantly low compared to the positive control, hydrogen peroxide. But extract from leaves showed high haemolytic effects at the concentrations of 500 μg/mL and 1000 μg/mL. Thus, extracts of S. glaucescens have antibacterial activity against several Gram-positive bacteria including Methicillin Resistant S. aureus with low haemolytic activity. At high concentrations, the extracts from leaves have toxicity risk. More studies for the active compounds are required for biological testing.